Scritture di infanzia e elaborazione del lutto - Franco Cambi (Firenze University Press, 2014)
To narrate childhood is going back to a lost "self", but a founding self of each subject. This tale is, at the same time, "mourning's processing" and "hermeneutic inquiry" and create writings full of meaning, on which the occidental culture gave us refined testimonials.